Dispersion of Sr and K Species Supported on CaO Eggshell-Based Catalysts for Biodiesel Production - Olvera-Ureña, E.; Rodriguez, J. A.; Díaz de León, J. N.; Tavizón-Pozos, J. A. (Topics in catalysis, 2025)
The dispersion of Sr and K supported on limestone-eggshell-based CaO support and its effect in the canola oil transesterification were studied in this work by changing the Sr/(Sr + K) molar ratios in 0.2, 0.3, and 0.4, keeping the K loading in 9 wt%. K and Sr were impregnated with methanol at 60 °C to the 50% limestone-eggshell CaO support and calcined at 800 °C. The characterization techniques used were TGA, XRD, SEM, XPS, and Hammet indicators. It was found that the interaction between K and Sr and its dispersion depends on the concentration of Sr. At Sr/(Sr + K) = 0.2, most of the Sr is introduced into the support, whereas the K remains on the surface. At Sr/(Sr + K) = 0.3, K and Sr interactions increased, and more Sr stayed on the surface as K 2 Sr(CO 3 ) 2 . However, as more Sr is added, Sr/(Sr + K) = 0.4, it also provokes K to enter the support. However, the number of active sites remained similar as agglomerates of this phase would form. Changing the reaction time, temperature, and MetOH/oil resulted in a 91% biodiesel yield at 90 min, 60 °C, and a MetOH/oil = 10. The chosen catalyst showed low stability since it was only active for two cycles.